METODE PENGOLAHAN AIR LIMBAH DOMESTIK UNTUK PENURUNAN KADAR AMONIA: STUDI LITERATUR - Sintya Dewi, Ni Luh Putu Intan; Dwipayanti, Ni Made Utami (ARCHIVE OF COMMUNITY HEALTH; Vol 8 No 3 (2021): Desember 2021DO - 10.24843/ACH.2021.v08.i03.p03, 2022)
ABSTRACT The high number of population growth and increased number of settlements can influences the amount of liquid waste discharged from household activities. Denpasar Sewerage Development Project (DSDP) part I and part II or the infrastructure development programs wich has a purpose to resolve the environmental pollution and sanitation problems in around Denpasar (Putera, dkk, 2019). Wastewater management that wich conducted by DSDP it is not effective towards ammonia removal. The aim of this research to find out alternative methods of domestic waste management that are effective against ammonia reduction based on the results of research that has been conducted over the past decade. The design of this study is Literature Review, data sources obtained from internet, then the data is synthesized using a narrative method by grouping data extraction results of the same type in accordance with the measured results to answer the aims of this research. The results of this study have been found four types of domestic waste water treatment methods based on the results of the Literature Review, the method is constructed wetland, activated sludge, biofilter, and chemical treatment methods. Keywords: Domestic Waste, Environmental Pollution, Sewage Treatment Systems, Effectiveness, Ammonia